Effects of the Global Financial Crisis - Chittedi, Krishna Reddy; Bathini, Santhosha (Indian Journal of Finance, 2009)
US sub prime crisis happens to be more serious as the synchronization effect has been larger because of globalization financial markets. The crisis, which started in the financial system, has been having adverse effect on the real economy. This paper analyzing recent trends in financial crisis and emphasizing on the severity of crisis in various segments of the real economy he came down the need for co-ordinated fiscal polices to come out of recession. The policymakers and Economists to rethink the model of 'privatization of profit and the socialization of cost'.